Rancang Bangun Sistem Pemantauan Panel Surya Berbasis Internet of Things - Kurniawan, Gede Widi; Agung, I G A Putu Raka; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i01.P17, 2023)
The application of the internet of things is starting to be widely used at this time. One of the developments in internet of things technology is monitoring a system with an Android application wirelessly. This study aims to design and build a solar panel monitoring system based on the Internet of things using the NodeMCU ESP32 developer board. The design of this system can make it easier for users to monitor solar panels in real time through an android application. The test is carried out by operating a solar panel monitoring system. Data from each sensor is compared with a comparison measure to get the difference in values. The results of the INA219 sensor test get an average difference in voltage of 0.09% and an average difference in current of 4.08%. The test results for the DHT11 sensor get an average difference in temperature of 0.77% and a difference in relative humidity of 1.82%. The results of testing the BH1750 sensor get an average difference in light intensity of 39.93%. This monitoring system can operate in accordance with the design and reading of data from sensors that have been sent to Firebase so that it can be seen in the Android application. Keyword— Solar panel; Internet of Things; Android; DHT11; INA219; BH1750; ESP32.